2023
DOI: 10.3390/pharmaceutics15020389
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole Cyclodextrin Based Polymeric Nanobeads for Enhanced Solubility and Activity: In Vitro/In Vivo and Molecular Simulation Approach

Abstract: Hydroxypropyl β-cyclodextrin (HPβCD) based polymeric nanobeads containing voriconazole (VRC) were fabricated by free radical polymerization using N, N′-methylene bisacrylamide (MBA) as a cross-linker, 2-acrylamide-2-methylpropane sulfonic acid (AMPS) as monomer and ammonium persulfate (APS) as reaction promoter. Optimized formulation (CDN5) had a particle size of 320 nm with a zeta potential of −35.5 mV and 87% EE. Scanning electron microscopy (SEM) depicted porous and non-spherical shaped beads. No evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The thermal properties of MA and HP-β-CD/MA microcapsules were determined using TAQ2000 (Waters, Framingham, MA, USA) differential scanning calorimeter [ 28 ]. A total of 4 mg of sample was placed onto the sample tray and heated from 30 °C to 300 °C at a rate of 10/min in the nitrogen environment.…”
Section: Methodsmentioning
confidence: 99%
“…The thermal properties of MA and HP-β-CD/MA microcapsules were determined using TAQ2000 (Waters, Framingham, MA, USA) differential scanning calorimeter [ 28 ]. A total of 4 mg of sample was placed onto the sample tray and heated from 30 °C to 300 °C at a rate of 10/min in the nitrogen environment.…”
Section: Methodsmentioning
confidence: 99%
“…Farooq M. et al demonstrated that by complexing voriconazole with HP-β-CD, no acute toxicity phenomena were observed after oral administration in experimental animals [ 43 ]. Another study investigated the clinical effects of voriconazole complexed with SBE-β-CD administered intravenously in 25 human patients with invasive aspergillosis.…”
Section: Benefits Of Inclusion Complexes (Cd–antifungal) In Antifunga...mentioning
confidence: 99%
“…At predefined intervals (0.5 to 12 h), the sample solution was removed from the receptor compartment and replaced with PBS. Finally, the absorption of samples was measured by uv/vis spectrophotometer (PerkinElmer Lambda 35, Riegelsville, PA, USA) at 229 nm, and different parameters such as permeation flux and enhancement ratio were calculated using Equations ( 4)-( 6) [37].…”
Section: Ex Vivo Skin Permeationmentioning
confidence: 99%